Semiactive control policies : ride analysis for passenger vehicles - Ihsan, Sany Izan (LAP LAMBERT Academic Publishing, 2011)
Comprehensive comparison on quarter-car, half-car and full-car models were conducted to analyze the effect of using semiactive control policies, namely skyhook, groundhook and hybrid controls, in improving ride quality of passenger vehicle. Sprung mass acceleration, suspension deflection and tire deflection responses were analyzed for measurements of ride quality, rattle-space and road holding. Three different analyses were conducted on each model; frequency-domain transfer function analysis, time-domain transient state and steady state analysis. Results shows that hybrid control policy gives significant improvements in most responses while at the same time it does not compromise road holding ability of vehicle. Further quantitative comparison of responses on all three models shows that quarter-car model is unable to accurately represent responses in full-car model. Half-car model gives reasonable representation of full-car model in some states. RMS analysis conducted on a H-car 2-DOF system shows good agreement to the previous work on Q-car 2-DOF. This book should benefit researchers working in the area of semiactive control of vehicle suspension system.